PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL DAN INTENSITAS MODAL TERHADAP KONSERVATISME AKUNTANSI (Studi Empiris pada Perusahaan Properties & Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2017 – 2022) - Setiawan, Destia Dwisakinah; Hunein, Hamida (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This study aims to provide empirical evidence of the influence of Institutional Ownership, Managerial Ownership, and Capital Intensity on Accounting Conservatism. This research uses a quantitative approach and the data used is secondary data. The population in this research is properties & real estate companies listed on the Indonesia Stock Exchange for the 2017-2022 period. The method for determining the sample uses purposive sampling. A sample of 7 companies was obtained over a 6 year period. The data analysis technique used is multiple linear regression analysis. The results of the F test show that simultaneously Institutional Ownership, Managerial Ownership and Capital Intensity have a significant effect on Accounting Conservatism. The results of the t test show that Managerial Ownership partially has no effect on Accounting Conservatism, but Institutional Ownership partially has a significant negative effect and Capital Intensity partially has a significant positive effect on Accounting Conservatism.